Contextual Fear Conditioning in Humans: Cortical-Hippocampal and Amygdala Contributions - Alvarez, Ruben P; Biggs, Arter; Chen, Gang; Pine, Daniel S; Grillon, Christian (The Journal of neuroscience, 2008)
Functional imaging studies of cued fear conditioning in humans have mostly confirmed findings in animals, but it is unclear whether the brain mechanisms that underlie contextual fear conditioning in animals are also preserved in humans. We investigated this issue using functional magnetic resonance imaging and virtual reality contexts. Subjects underwent differential context conditioning in which they were repeatedly exposed to two contexts (CXT+ and CXT-) in semirandom order, with contexts counterbalanced across participants. An unsignaled footshock was consistently paired with the CXT+, and no shock was ever delivered in the CXT-. Evidence for context conditioning was established using skin conductance and anxiety ratings. Consistent with animal models centrally implicating the hippocampus and amygdala in a network supporting context conditioning, CXT+ compared with CXT- significantly activated right anterior hippocampus and bilateral amygdala. In addition, context conditioning was associated with activation in posterior orbitofrontal cortex, medial dorsal thalamus, anterior insula, subgenual anterior cingulate, and parahippocampal, inferior frontal, and parietal cortices. Structural equation modeling was used to assess interactions among the core brain regions mediating context conditioning. The derived model indicated that medial amygdala was the source of key efferent and afferent connections including input from orbitofrontal cortex. These results provide evidence that similar brain mechanisms may underlie contextual fear conditioning across species.